Recruitment of PLANT U-BOX13 and the PI4Kβ1/β2 Phosphatidylinositol-4 Kinases by the Small GTPase RabA4B Plays Important Roles during Salicylic Acid-Mediated Plant Defense Signaling in Arabidopsis. Issue 1 (29th January 2015) - Antignani, Vincenzo; Klocko, Amy L.; Bak, Gwangbae; Chandrasekaran, Suma D.; Dunivin, Taylor; Nielsen, Erik
Abstract : A small Rab GTPase orchestrates salicylic acid-mediated defense responses by recruiting Rab effector proteins that normally suppress these defense responses in uninfected plants. Abstract: Protection against microbial pathogens involves the activation of cellular immune responses in eukaryotes, and this cellular immunity likely involves changes in subcellular membrane trafficking. In eukaryotes, members of the Rab GTPase family of small monomeric regulatory GTPases play prominent roles in the regulation of membrane trafficking. We previously showed that RabA4B is recruited to vesicles that emerge from trans-Golgi network (TGN ) compartments and regulates polarized membrane trafficking in plant cells. As part of this regulation, RabA4B recruits the closely related phosphatidylinositol 4-kinase (PI4K) PI4Kβ1 and PI4Kβ2 lipid kinases. Here, we identify a second Arabidopsis thaliana RabA4B-interacting protein, PLANT U-BOX13 (PUB13), which has recently been identified to play important roles in salicylic acid (SA )-mediated defense signaling. We show that PUB13 interacts with RabA4B through N-terminal domains and with phosphatidylinositol 4-phosphate (PI-4P ) through a C-terminal armadillo domain. Furthermore, we demonstrate that a functional fluorescent PUB13 fusion protein (YFP-PUB13) localizes to TGN and Golgi compartments and that PUB13, PI4Kβ1, and PI4Kβ2 are negative regulators of SA -mediated induction of pathogenesis-related gene expression. Taken together, these results highlight a role for RabA4B and PI-4P in SA -dependent defense responses.